Magkukuwento na si Lola ng mga kuwento ni Lola Basyang sa libro, teatro, telebisyon at radyo - Bellen, Christine S. (2009)
This paper analyzes how the popular stories of Severino Reyes have been translated into various forms of media. After Gilda Cordero-Fernando translated the story into English in 1997 for Tahanan Books, Lola Basyang stories became even more a part of children's literature. On the other hand, the publication of Lola Basyang picture books in 2004-2005 and 2007 paved the way for the stories to be adapted for dance, theater, television, and radio. Each of these media required different ways of adapting the classic stories.